Anatomia del potere nella Chiesa cattolica - Guzzo, Luigi Mariano ca. 20./21. Jh. (Rassegna di teologia, 2025)
The contribution investigates the issue of power within the Catholic Church. Criticism is directed at the current model of power, highlighting how, despite the Second Vatican Council having promoted the principle of baptismal equality, the exercise of power remains firmly anchored in the hands of the hierarchical apparatus. The article also focuses on the transformations of the potestas iurisdictionis and on the emerging tensions between the traditional conception of power and the push towards a more synodal and participatory Church.